APPROX – mutual approximations between the Galilean moons: the 2016–2018 observational campaign. Issue 4 (29th November 2018) - Morgado, B; Vieira-Martins, R; Assafin, M; Machado, D I; Camargo, J I B; Sfair, R; Malacarne, M; Braga-Ribas, F; Robert, V; Bassallo, T; Benedetti-Rossi, G; Boldrin, L A; et al.
ABSTRACT: The technique of mutual approximations accurately gives the central instant of the maximum apparent approximation of two moving natural satellites in the plane of the sky. This can be used in ephemeris fitting to infer the relative positions of satellites with high precision. Only mutual phenomena – occultations and eclipses – can achieve better results. However, mutual phenomena only occur every six years in the case of Jupiter. Mutual approximations do not have this restriction and can be observed at any time in the year as long as the satellites are visible. In this work, we present 104 central instants determined from the observations of 66 mutual approximations between the Galilean moons carried out at different sites in Brazil and France during the period 2016–2018. For 28 events, we have at least two independent observations. All telescopes were equipped with a narrow-band filter centred at 889 nm with a width of 15 nm to eliminate the scattered light from Jupiter. The telescope apertures ranged between 25 and 120 cm. For comparison, the precision of the positions obtained with classical CCD astrometry is about 100 mas, for mutual phenomena it can be 10 mas or less, and the average internal precision obtained with mutual approximations is 11.3 mas. This new type of simple, yet accurate, observations can significantly improve the orbits and ephemeris of Galilean satellites and thus it can be very useful for the planning of future space missions to the Jovian system.